Dinosaur - Norman, David, 1952-; Milner, Angela C.; Keates, Colin (New York : Knopf : Distributed by Random House, 1989)
Text and photographs explore the world of the dinosaurs, focusing on such aspects as their teeth, feet, eggs, and fossils.
Includes index.
Keywords: Dinosaurs -- Juvenile literature; Dinosaurs; Fossils; Paleontology